Effects of Obesity and Exercise on Hepatic and Pancreatic Lipid Content and Glucose Metabolism : PET Studies in Twins Discordant for BMI - Lietzén, Martin S.; Mari, Andrea; Ojala, Ronja; Hentilä, Jaakko; Koskensalo, Kalle; Lautamäki, Riikka; Löyttyniemi, Eliisa; Parkkola, Riitta; Saunavaara, Virva; Kirjavainen, Anna K.; Rajander, Johan; Malm, Tarja; et al. (MPDI, 2025)
Obesity and sedentarism are associated with increased liver and pancreatic fat content (LFC and PFC, respectively) as well as impaired organ metabolism. Exercise training is known to decrease organ ectopic fat but its effects on organ metabolism are unclear. Genetic background affects susceptibility to obesity and the response to training. We studied the effects of regular exercise training on LFC, PFC, and metabolism in monozygotic twin pairs discordant for BMI. We recruited 12 BMI-discordant monozygotic twin pairs (age 40.4, SD 4.5 years; BMI 32.9, SD 7.6, 8 female pairs). Ten pairs completed six months of training intervention. We measured hepatic insulin-stimulated glucose uptake using [18F]FDG-PET and fat content using magnetic resonance spectroscopy before and after the intervention. At baseline LFC, PFC, gamma-glutamyl transferase (GT), and hepatic glucose uptake were significantly higher in the heavier twins compared to the leaner co-twins (p = 0.018, p = 0.02 and p = 0.01, respectively). Response to training in liver glucose uptake and GT differed between the twins (Time*group p = 0.04 and p = 0.004, respectively). Liver glucose uptake tended to decrease, and GT decreased only in the heavier twins (p = 0.032). In BMI-discordant twins, heavier twins showed higher LFC and PFC, which may underlie the observed increase in liver glucose uptake and GT. These alterations were mitigated by exercise. The small number of participants makes the results preliminary, and future research with a larger pool of participants is warranted.